Rule-Based Specification of Auction Mechanisms - Lochner, Kevin M.; Wellman, Michael P. (Autonomous Agents and Multiagent Systems: Proceedings, 3rd International Joint Conference, New York City, New York, 2004., 2004)
Machine-readable specifications of auction mechanisms facilitate configurable implementation of computational markets, as well as standardization and formalization of the auction design space. We present an implemented rule-based scripting language for auctions, which provides constructs for specifying temporal control structure, while supporting orthogonal definition of mechanism policy parameters. Through a series of examples, we show how the language can capture much of the space of single-dimensional auctions, and can be extended to cover other novel designs.